USING STRATEGIES OF SPEAKING SKILLS FOR BUILDING CONFIDENCE OF SECONDARY SCHOOL LEARNERS - Alijonova Muxlisa (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This study examines the role of speaking strategies in building the confidence of secondary school learners in foreign language acquisition. It focuses on various techniques such as role-plays, peer interactions, and real-life simulations to enhance students’ speaking skills and self-assurance. A qualitative research approach was employed, incorporating classroom observations, student surveys, and teacher interviews. The findings suggest that implementing targeted speaking strategies significantly improves learners’ confidence, enabling them to engage more actively in communication. The study highlights the importance of creating a supportive environment and providing students with frequent speaking opportunities to foster their language development and boost their confidence in using the language.